The role of online mass media as a tool for the 2019 political campaign in Indonesia - Fadhlurrohman, Mochammad Iqbal; Purnomo, Eko Priyo (Faculty of Communications Science, Dr. Soetomo University, 2020)
Media is a tool to provide information to be broadcasted or circulated openly to the public. In the technology era, the has a very media significant role because it can influence the public’s opinion as the society cannot be separated from technology. During the ‘New Order’ era, the authorities had censored the truth, thus forced the public to initiate regime changes that brought down the new order rulers. Then, the reformation era emerged, which prioritised public freedom, including freedom of the press and freedom of expression. This study used qualitative analysis assisted with the NVivo12 Plus application in the data analysis. The data was obtained from the internet, websites, and journals. This study explained a form of a political campaign that used the influence and impact of media to lead public opinion. This research also looked at the role of the mass media –mainly online media– in the 2019 political campaign. We found that the media’s influence and role are significant and reliable to win votes and political contestation. In addition, the research also provided information about the 2019 presidential election.